Function of a Chemotaxis-Like Signal Transduction Pathway in Modulating Motility, Cell Clumping, and Cell Length in the Alphaproteobacterium Azospirillum brasilense - Bible, Amber N. (American Society for Microbiology (ASM), 2008)
A chemotaxis signal transduction pathway (hereafter called Che1) has been previously identified in the alphaproteobacterium Azospirillum brasilense. Previous experiments have demonstrated that although mutants lacking CheB and/or CheR homologs from this pathway are defective in chemotaxis, a mutant in which the entire chemotaxis pathway has been mutated displayed a chemotaxis phenotype mostly similar to that of the parent strain, suggesting that the primary function of this Che1 pathway is not the control of motility behavior. Here, we report that mutants carrying defined mutations in the cheA1 (strain AB101) and the cheY1 (strain AB102) genes and a newly constructed mutant lacking the entire operon [Δ(cheA1-cheR1)::Cm] (strain AB103) were defective, but not null, for chemotaxis and aerotaxis and had a minor defect in swimming pattern. We found that mutations in genes of the Che1 pathway affected the cell length of actively growing cells but not their growth rate. Cells of a mutant lacking functional cheB1 and cheR1 genes (strain BS104) were significantly longer than wild-type cells, whereas cells of mutants impaired in the cheA1 or cheY1 genes, as well as a mutant lacking a functional Che1 pathway, were significantly shorter than wild-type cells. Both the modest chemotaxis defects and the observed differences in cell length could be complemented by expressing the wild-type genes from a plasmid. In addition, under conditions of high aeration, cells of mutants lacking functional cheA1 or cheY1 genes or the Che1 operon formed clumps due to cell-to-cell aggregation, whereas the mutant lacking functional CheB1 and CheR1 (BS104) clumped poorly, if at all. Further analysis suggested that the nature of the exopolysaccharide produced, rather than the amount, may be involved in this behavior. Interestingly, mutants that displayed clumping behavior (lacking cheA1 or cheY1 genes or the Che1 operon) also flocculated earlier and quantitatively more than the wild-type cells, whereas the mutant lacking both CheB1 and CheR1 was delayed in flocculation. We propose that the Che1 chemotaxis-like pathway modulates the cell length as well as clumping behavior, suggesting a link between these two processes. Our data are consistent with a model in which the function of the Che1 pathway in regulating these cellular functions directly affects flocculation, a cellular differentiation process initiated under conditions of nutritional imbalance.